Comparison of the effect of semen from HIV-infected and uninfected men on CD4+ T-cell infection. (15th May 2016) - Camus, Céline; Matusali, Giulia; Bourry, Olivier; Mahe, Dominique; Aubry, Florence; Bujan, Louis; Pasquier, Christophe; Massip, Patrice; Ravel, Célia; Zirafi, Onofrio; Munch, Jan; Roan, Nadia R.; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objectives: Semen composition is influenced by HIV-1 infection, yet the impact of semen components on HIV infection of primary target cells has only been studied in samples from HIV-uninfected donors. Design: We compared the effect of seminal plasma (SP) from chronically HIV-infected (SP+) versus uninfected donors (SP–) on HIV-1 infection of peripheral blood mononuclear cells (PBMCs) and CD4 + T cells. Methods: Primary cells were infected with HIV-1 in the presence of SP+ or SP– and analyzed for infection level, metabolic activity, HIV receptor expression, proliferation and activation. SP+ and SP– were compared for infection-enhancing peptides, cytokines and prostaglandin E2 levels. Results: SP– efficiently enhanced HIV-1 R5 infection of CD4 + T cells, whereas SP+ enhancing activity was significantly reduced. RANTES (CCL5) concentrations were elevated in SP+ relative to SP–, whereas the concentrations of infectivity-enhancing peptides [semen-derived enhancer of viral infection (SEVI), SEM1, SEM2] were similar. CCR5 membrane expression levels were reduced on CD4 + T cells shortly postexposure to SP+ compared with SP– and correlated to R5-tropic HIV-1 infection levels, and CCR5 ligands' concentrations in semen. SP+ and SP– displayed similar enhancing activity on PBMC infection by X4-tropic HIV-1. Addition/depletion of RANTES (regulated on activation, normal T-cell expressed and secreted) from SPs modulated their effect on PBMC infection by R5-tropic HIV-1. Conclusion: Semen from HIV-infected donors exhibits a significantly reduced enhancing potential on CD4 + T-cell infection by R5-tropic HIV-1 when compared with semen from uninfected donors. Our data indicate that elevated seminal concentrations of RANTES in HIV-infected men can influence the ability of semen to enhance infection.